A systematic review of predictors of suicidal thoughts and behaviors among autistic adults: Making the case for the role of social connection as a protective factor. (February 2023) - Mournet, Annabelle M.; Wilkinson, Ellen; Bal, Vanessa H.; Kleiman, Evan M.
Abstract: Autistic adults are a high-risk population for suicidal thoughts and behaviors (STBs). Accordingly, this systematic review aims to review the prevalence of STBs among autistic adults, review the risk and protective factors for STBs in autistic adults, and formulate a disorder-specific conceptualization of risk in this population. We systematically searched PsycINFO and Google Scholar for all studies published prior to March 28th, 2022. We included empirical articles focused on autistic adults, ages 18 years and older, reporting on suicide-related outcomes. In total, 45 peer-reviewed empirical articles were included in the current systematic review. The most frequently studied factors in relation to suicide risk among autistic adults were interpersonal constructs (42.4% of total studies looking at risk/protective factors) and depressive symptoms (36.4% of total studies looking at risk/protective factors). We conclude by summarize two key content areas: exploring social and interpersonal constructs and better understanding the role of depressive symptoms in autism. As researchers continue to explore STBs among autistic adults, it will be necessary to addressing the overreliance on autistic symptoms instead of autism diagnoses, measurement issues of STBs, and a need for treatment adaptations. Highlights: Autistic adults are a high-risk population for suicidal thoughts and behaviors. 45 empirical articles were included in the current systematic review. The most frequently studied factors were interpersonal constructs and depression.